Dynamic Archiving Information System (SIKD) For Company Operational Effectiveness Pt. Jakarta Industrial Estate Pulogadung (Persero) - Nanda Salsabila Putri Harsya; Al Hasin (Cita konsultindo, 2025)
This study analyzes the implementation of Dynamic Archiving Information System (SIKD) at PT Jakarta Industrial Estate Pulogadung (PT JIEP) to improve operational effectiveness. SIKD replaces manual methods in archive management, thereby accelerating document searches, improving data security, and reducing paper use. This study uses a qualitative approach through observation, interviews, and fishbone diagram analysis. The results of the study indicate that Dynamic Archiving Information System (SIKD) improves time efficiency, employee productivity, and transparency and accountability of company operations. However, there are obstacles such as dependence on internet connection and lack of employee training. Other technical obstacles include limited document re-registration features (backdate) and suboptimal system capacity. To improve the effectiveness of SIKD, it is recommended to improve technology infrastructure, continuous training, and update features to make them more user-friendly. With these steps, SIKD can be more optimal in supporting PT JIEP's operations.